(untitled) (Global Journal of Medical Research, 2015)
This case report discusses a 26 year old patient diagnosed with Type 2 Neurofibromatosis (NF), who has a twin sister. The patient exhibits infantile encephalopathy, mental retardation and type 2 NF, while her twin sister is perfectly healthy and does not exhibit any lesions on the neuroimaging examination.